2015
DOI: 10.1210/me.2014-1324
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Gq/11 in the Mouse Corpus Luteum Is Required for Parturition

Abstract: Mice with a deletion of Gα(q/11) in granulosa cells were previously shown to be subfertile. They also have a reduced ovulatory response due to a deficiency in the ability of the activated LH receptor to fully induce the granulosa cell progesterone receptor. Because this conditional deletion of Gα(q/11) will interfere with the actions of any G protein-coupled receptor that activates G(q/11) in granulosa or luteal cells, we sought to determine whether the actions of other hormones that contribute to fertility we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 57 publications
1
28
0
Order By: Relevance
“…Likewise, protein expression of NR4A1, the most downstream component of the PGF 2α signaling pathway that directly binds to the Akr1c18 promoter, remained unaffected in KO mice ovaries. Thus, the function of MAMLD1 appears to be independent of the PGF 2α signaling pathway, although mRNA expression of the Gq/11 protein family, a recently identified component of this pathway 11 , was not analyzed in the present study. In contrast, Stat5b and Prlr were markedly upregulated in KO mice ovaries.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Likewise, protein expression of NR4A1, the most downstream component of the PGF 2α signaling pathway that directly binds to the Akr1c18 promoter, remained unaffected in KO mice ovaries. Thus, the function of MAMLD1 appears to be independent of the PGF 2α signaling pathway, although mRNA expression of the Gq/11 protein family, a recently identified component of this pathway 11 , was not analyzed in the present study. In contrast, Stat5b and Prlr were markedly upregulated in KO mice ovaries.…”
Section: Discussionmentioning
confidence: 90%
“…Of these, prostaglandin F2α (PGF 2α ) upregulates Akr1c18 via a signaling pathway consisting of PGF 2α , PGF 2α receptor (FP), JUND, and nuclear receptor subfamily 4 group A member 1 (NR4A1, also known as NUR77) 1 9 10 . The Gq/11 protein family also serves as a component of the PGF 2α signaling pathway 11 . Genetic knockout (KO) of Akr1c18 , Fp , or Gα q/11 leads to persistent progesterone production and subsequent parturition failure 5 11 12 13 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A role for FP has also been demonstrated in regulating blood pressure where its blockade has been suggested to reduce blood pressure (62). FP is involved in parturition with enhanced PGF2␣ signaling initiating labor by causing smooth muscle contraction of the myometrium (63,64). The AT1R is also expressed in the myometrium with increased levels coinciding with pregnancy (65)(66)(67).…”
Section: Allosteric Interactions In Gpcr Heterodimersmentioning
confidence: 99%
“…Studies with mice harboring a granulosa/luteal cell-specific deletion of G α q/11 have demonstrated that the differentiation of granulosa cells into luteal cells, as well as the establishment and maintenance of pregnancy, does not require G q/11 [ 3 , 4 ]. Parturition, on the other hand, is dependent on the prostaglandin F2α (PGF2α)-provoked activation of luteal G q/11 [ 4 ]. A conditional deletion of G α q/11 from granulosa/luteal cells disrupts the actions of PGF2α on luteal cells that normally occur toward the end of gestation [ 4 ].…”
Section: Introductionmentioning
confidence: 99%